Achieving the sustainable development goals in agriculture: The crucial role of nitrogen in cereal-based systems - Ladha, Jagdish K; Jat, Mangi Lal; Stirling, Clare M; Chakraborty, Debashis; Pradhan, Prajal; Krupnik, Timothy J.; Sapkota, Tek Bahadur; Pathak, Himanshu; Rana, Dharamvir Singh; Tesfaye, Kindie; Gerard, Bruno G. (Elsevier, 2020)
The crucial link between agricultural growth and the Sustainable Development Goals (SDGs) set by the United Nations Development Programme is established through efficient use of nitrogen in the cereal production systems. Nitrogen, mostly in its reactive form as fertilizer or synthetic N, governs the food production, and reconciles the productivity with economic and environmental considerations. However, N flows in the production system involves a large N leaking to the environment resulting in abysmally low nitrogen use efficiencies and environmental adversity. Agricultural system with sub-optimal N application is characterized with low crop productivity, spiraling into the vicious cycle of poverty, malnutrition and poor economy, a case most common in the sub-Saharan Africa. These essentially relate to SDG 1 (no-poverty), 2 (zero-hunger), 3 (good health and well-being), 8 (decent work and economic growth) and 15 (life on land). Excess or imbalanced fertilizer N in most of China and parts of India led to serious environmental hazards, degradation of land and economic loss. Balancing the amount of N input in these regions will contribute in achieving the SDG 13 (climate action). Meeting some of the SDGs (5, gender equality; 6, clean water and sanitation; 10: reduced inequalities; etc.) requires optimum N application, which will also ensure “responsible consumption and production” (SDG 12). The quest for an appropriate N management needs accounting for the N surplus in a production system, and evolving strategies for increasing the nitrogen use efficiency. Much effort has been made to this effect with varying success. Cutting-edge technological options are although available on the horizon, the success lies in improved awareness among the policy makers, stakeholders and farmers, and better research to quantify the linkage between N management and the SDGs, taking collectively.